A multi-site proof-of-concept investigation of computerized approach-avoidance training in adolescent cannabis users. (1st June 2018) - Jacobus, Joanna; Taylor, Charles T.; Gray, Kevin M.; Meredith, Lindsay R.; Porter, Anna M.; Li, Irene; Castro, Norma; Squeglia, Lindsay M.
Highlights: Youth decrease cannabis use after Cannabis Approach Avoidance Training. Youth increase alcohol use after Cannabis Approach Avoidance Training. Multisite computerized intervention trials with youth cannabis users are feasible. Future computerized interventions should target youth cannabis and alcohol use. Abstract: Background: Few effective treatment options exist for cannabis-using youth. This pilot study aimed to test Approach-Avoidance Training to reduce cannabis use with non-treatment-seeking adolescents. Methods: Eighty cannabis-using non-treatment-seeking adolescents (average age 19) were recruited from San Diego, California and Charleston, South Carolina, and randomized to complete either six sessions of Cannabis Approach-Avoidance Task Training (CAAT-training) designed to reduce automatic approach biases for cannabis cues or CAAT-sham training. Change in two primary outcome variables was examined: 1) cannabis approach bias and 2) percent cannabis use days over study enrollment. Change in percent alcohol use days over study enrollment was explored as a secondary outcome. Results: A mixed models repeated measures analysis confirmed the group by time interaction effect for approach bias failed to reach statistical significance ( p  = .06). Significant group by time interaction effects ( p s < 0.05) predicted percent days of cannabis and alcohol use over study enrollment. Participants randomized to the avoid cannabis condition (CAAT-training) reported 7% fewer days of cannabis use compared to 0% change for sham; unexpectedly, those in the avoid cannabis condition reported 10% percent more alcohol use days compared to 3% more for sham. Conclusions: Computerized cognitive bias modification paradigms may have utility in reducing adolescent cannabis use. Future work should consider developing a paradigm that addresses both cannabis and alcohol, as well as alternative computerized approaches for coping with addictive behavior in conjunction with bias modification.